2020
DOI: 10.1007/s12094-020-02295-w
|View full text |Cite
|
Sign up to set email alerts
|

SEOM clinical guidelines for the treatment of small-cell lung cancer (SCLC) (2019)

Abstract: Small-cell lung cancer (SCLC) accounts for 15% of lung cancers. Only one-third of patients are diagnosed at limited stage. The median survival remains to be around 15-20 months without significative changes in the strategies of treatment for many years. In stage I and IIA, the standard treatment is the surgery followed by adjuvant therapy with platinum-etoposide. In stage IIB-IIIC, the recommended treatment is early concurrent chemotherapy with platinum-etoposide plus thoracic radiotherapy followed by prophyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 39 publications
2
62
0
1
Order By: Relevance
“…The median PFS is only 5.5 months and the median OS is less than 10 months. The therapeutic effect remains unsatisfactory following first-line treatment progress, and the 1-year OS rate of topotecan as a second-line therapy is only 30% (13)(14)(15)(16). With the rapid development of immunotherapy; IMpower133, CASPIAN, and other experimental results have shown that immunotherapy combined with standard chemotherapy was able to break through the median OS of SCLC for 12 months, and the NCCN recommended it as a first-line treatment for SCLC in 2019 (17).…”
Section: Discussionmentioning
confidence: 99%
“…The median PFS is only 5.5 months and the median OS is less than 10 months. The therapeutic effect remains unsatisfactory following first-line treatment progress, and the 1-year OS rate of topotecan as a second-line therapy is only 30% (13)(14)(15)(16). With the rapid development of immunotherapy; IMpower133, CASPIAN, and other experimental results have shown that immunotherapy combined with standard chemotherapy was able to break through the median OS of SCLC for 12 months, and the NCCN recommended it as a first-line treatment for SCLC in 2019 (17).…”
Section: Discussionmentioning
confidence: 99%
“…The Veteran's Administration Lung Cancer Study Group categorizes SCLC into limitedstage and extensive-stage, with the differentiating feature being whether disease is limited to one hemithorax and therefore encompassable within a feasible radiation field. In less than 5% of cases, SCLC may be diagnosed in very early stages, wherein guidelines recommend definitive surgical resection followed by platinum-based adjuvant chemotherapy for stage I and selected stage IIA patients [2,3]. Otherwise, the mainstay of treatment for limited-stage SCLC (LS-SCLC) is concurrent chemoradiation (CRT) and prophylactic cranial irradiation (PCI).…”
Section: Introductionmentioning
confidence: 99%
“…SCLC had limit therapeutic methods, which also had faster doubling time, higher growth fraction, and earlier development of extensive transfer [2]. The median overall survival (OS) for extensive-stage SCLC was 9 ~ 11 months [3,4]. The chance of surgery is generally lost because SCLC often develops distant metastases when discovered.…”
Section: Introductionmentioning
confidence: 99%
“…The chance of surgery is generally lost because SCLC often develops distant metastases when discovered. Despite sensitive to initial platinum-based chemotherapy (up to 75%), ES-SCLC patients would progress during the rst months mostly (platinum-sensitive ≥ three months, platinum-resistant < three months) [3,4]. Molecular hallmarks of SCLC have revealed an extremely high mutation rate and rare oncogenic drivers [5], so the application of targeted therapy in SCLC is limited.…”
Section: Introductionmentioning
confidence: 99%